Internalisasi Nilai Ketaatan, Kompetisi dalam Kebaikan, dan Etos Kerja sebagai Strategi Pendidikan Karakter Islam - m. basor hidayatullah lubis; M. Rizky Fajri; Ridwal Trisoni; Muhamad Yahya (Jurnal Media Ilmu, 2025)
This study aims to analyze the internalization of the values of obedience, competition in good deeds, and Islamic work ethic as a strategy for strengthening students’ Islamic character through the Mutaba’ah Yaumiyah program, as well as to examine the collaborative role of teachers and parents in this process. The research employed a qualitative approach using a case study design. Participants included Islamic Religious Education teachers, parents, and students involved in the implementation of the Mutaba’ah Yaumiyah program. Data were collected through in-depth interviews, observations, and documentation, and analyzed using the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing.The findings reveal that the Mutaba’ah Yaumiyah program effectively internalizes Islamic character values through structured habituation of daily worship monitored collaboratively by teachers and parents. The program contributes to improvements in three main domains: religious obedience, social morality, and religious independence. Students demonstrate greater consistency in performing obligatory and voluntary prayers, regular Qur’an recitation, polite behavior, emotional self-control, and social responsibility. In addition, the program strengthens communication and partnership between schools and families.The novelty of this study lies in its emphasis on systematic and continuous monitoring of daily worship practices as a practical mechanism for character internalization, integrating school-based instruction with family-based supervision. The findings imply that Mutaba’ah Yaumiyah can serve as an effective and replicable strategy in Islamic Religious Education to foster sustainable religious character development from an early age through strong school family collaboration.